2021
DOI: 10.1007/s00392-021-01910-2
|View full text |Cite|
|
Sign up to set email alerts
|

SARS-CoV-2, myocardial injury and inflammation: insights from a large clinical and autopsy study

Abstract: Objective Despite growing evidence about myocardial injury in hospitalized COronaVIrus Disease 2019 (COVID-19) patients, the mechanism behind this injury is only poorly understood and little is known about its association with SARS-CoV-2-mediated myocarditis. Furthermore, definite evidence of the presence and role of SARS-CoV-2 in cardiomyocytes in the clinical scenario is still lacking. Methods We histologically characterized myocardial tissue of 40 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
1
28
0
1
Order By: Relevance
“…After excluding duplicates and preliminary screening, 155 full-text articles were assessed for eligibility, and 141 studies were excluded for not meeting the inclusion criteria, leaving 13 studies fulfilling the inclusion criteria ( Figure 1 , Supplementary File 2 ). 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19
Figure 1 Flow diagram of selected studies for the meta-analysis according to the PRISMA. PRISMA = Preferred Reporting Items for Systematic Reviews and Meta-Analyses.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding duplicates and preliminary screening, 155 full-text articles were assessed for eligibility, and 141 studies were excluded for not meeting the inclusion criteria, leaving 13 studies fulfilling the inclusion criteria ( Figure 1 , Supplementary File 2 ). 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19
Figure 1 Flow diagram of selected studies for the meta-analysis according to the PRISMA. PRISMA = Preferred Reporting Items for Systematic Reviews and Meta-Analyses.
…”
Section: Resultsmentioning
confidence: 99%
“… 9 Zambia 21 40 (12.3) 14 (66.2 %) 3 (14.3 %) 3 (14.3 %) 1 (4.8 %) NR NR 3 (14.2 %) Dal Ferro et al. 10 Italy 40 79 (11) 22 (55 %) NR 15 (37 %) 10 (24 %) NR NR NR Romanova et al. 11 Russia 42 69 (15) † 72 (15) ‡ 22 (52.3 %) 17 (40.4 %) 38 (90.4 %) 11 (26.1 %) NR NR NR Bryce et al.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…In this scenario, acute myocarditis may be responsible for the myocardial damage. This issue has been reported in several case reports, some of them also testing myocardial tissue by endomyocardial biopsy or post-mortem autopsy [ 7 •, 19 ]. However, in none of these cases a direct cause–effect relation between COVID-19 and acute cardiac inflammatory disease has been reported.…”
Section: Assessment Of Cardiovascular Damage: How and Whenmentioning
confidence: 89%
“…Interestingly, viral genome and Spike protein were not found in heart samples of patients with myocarditis. Authors suggested, supported by histopathological findings, that acute hypoxic cardiomyopathy, or the combination of acute hypoxia and pre-existing cardiac disease, along with a cytokine storm, is the main culprits of COVID-19-related cardiac injury [ 19 ].…”
Section: Outcomes Of Patients With Covid-19 and Cardiovascular Involv...mentioning
confidence: 99%